MOTIVACIONAL FACTORS FOR THE PRACTICE OF PHYSICAL EXERCISES AMONG REGULAR AT OUTDOOR FITNESS CNETES IN AMAMBAI-MS (Fiep Bulletin - online, 2013)
Identify the mainly motivational factors for the practice of physical exercising among regulars at outdoor fitness centers in Amambai-MS. The exploratory study, having a transverse character, with 23 regulars of the outdoor fitness centers related to the city already mentioned, of both gender, showed the results on the methods: qualitative, when the interviewed were stimulated to think freely related to the theme here approached, to their object or concept, meantime the protocol open questions; and quantitative, for the percentage of the results acquired on the closed questions. 44% of the regulars answered that they attend the outdoor fitness centers “to be healthy”, making it possible to understand that this is the most important factor that motivates them to practice physical exercise, in a second place, but not less important, “losing weight” is what makes 31% of the people to this kind of training, and improving the muscle tone with 18% of them. The other 7% left use this practice to keep the weight, improve the asthmatic bronchitis and the anxiety, regular the arterial pressure, among others. Every practice must be orientated for the Physical Education Professional and it is necessary that the Public Power attempt for the need of the presence of this professional on the public areas offered for the physical training of the citizens who deserve this service for the acquirement of health and/or for the prevention of illness.
Keywords: Fitness center; Outdoor; Exercises.